The Paradox of Environmental Symbiont Acquisition in Obligate Mutualisms - Hartmann, Aaron C; Baird, Andrew H; Knowlton, Nancy; Huang, Danwei (Current biology, 2017)
Mutually beneficial interactions between species (mutualisms) shaped the evolution of eukaryotes and remain critical to the survival of species globally [1, 2]. Theory predicts that hosts should pass mutualist symbionts to their offspring (vertical transmission) [3-8]. However, offspring acquire symbionts from the environment in a surprising number of species (horizontal acquisition) [9-12]. A classic example of this paradox is the reef-building corals, in which 71% of species horizontally acquire algal endosymbionts [9]. An untested hypothesis explaining this paradox suggests that horizontal acquisition allows offspring to avoid symbiont-induced harm early in life. We reconstructed the evolution of symbiont transmission across 252 coral species and detected evolutionary transitions consistent with costs of vertical transmission among broadcast spawners, whose eggs tend to be positively buoyant and aggregate at the sea surface. Broadcasters with vertical transmission produce eggs with traits that favor reduced buoyancy (less wax ester lipid) and rapid development to the swimming stage (small egg size), both of which decrease the amount of time offspring spend at the sea surface. Wax ester provisioning decreased after vertically transmitting species evolved brooding from broadcasting, indicating that reduced buoyancy evolves only when offspring bear symbionts. We conclude that horizontal acquisition protects offspring from damage caused by high light and temperatures near the sea surface while providing benefits from enhanced fertilization and outcrossing. These findings help explain why modes of symbiont transmission and reproduction are strongly associated in corals and highlight benefits of delaying mutualist partnerships, offering an additional hypothesis for the pervasiveness of this theoretically paradoxical strategy.